The Effect of Soft Skills and Hard Skills on Student Work Readiness Bisnis Digital STMIK Pelita Nusantara Medan - Sinulingga, Nora; Irwanda, Hendy; Monika, Bella (Universitas Negeri Medan, 2023)
The world of work is currently growing so that it has an impact on the skills needed to achieve a better career. Every college graduate is expected to excel and be skilled at work and have full competence within himself. An educational institution becomes a main pillar in producing competent graduates who have hard skills, soft skills. This study seeks to determine the impact of hard skills and soft skills on the work readiness of students majoring in Digital Business at STMIK Pelita Nusantara. Forty students were surveyed using a non-probability sampling technique and a questionnaire.